Incorporation of a Machine Learning Algorithm With Object Detection Within the Thyroid Imaging Reporting and Data System Improves the Diagnosis of Genetic Risk - Wang, Shuo; Xu, Jiajun; Tahmasebi, Aylin; Daniels, Kelly; Liu, Ji-Bin; Curry, Joseph; Cottrill, Elizabeth; Lyshchik, Andrej; Eisenbrey, John R. (Frontiers in Oncology, 2020)
Background: The role of next generation sequencing (NGS) for identifying high risk mutations in thyroid nodules following fine needle aspiration (FNA) biopsy continues to grow. However, ultrasound diagnosis even using the American College of Radiology’s Thyroid Imaging Reporting and Data System (TI-RADS) has limited ability to stratify genetic risk. The purpose of this study was to incorporate an artificial intelligence (AI) algorithm of thyroid ultrasound with object detection within the TI-RADS scoring system to improve prediction of genetic risk in these nodules. Methods: 252 nodules from 249 patients that underwent ultrasound imaging and ultrasound-guided FNA with NGS with or without resection were retrospectively selected for this study. A machine learning program (Google AutoML) was employed for both automated nodule identification and risk stratification. 201 nodules were used for model training and 51 reserved for testing. Three blinded radiologists scored the images of the test set nodules using TI-RADS and assigned each nodule as high or low risk based on the presence of highly suspicious imaging features on TI-RADS (very hypoechoic, taller-than-wide, extra-thyroidal extension, punctate echogenic foci). Subsequently, the TI-RADS classification was modified to incorporate AI for T4 nodules while treating T1-3 as low risk and T5 as high risk. All diagnostic predictions were compared to the presence of a high-risk mutation and pathology when available. Results: The AI algorithm correctly located all nodules in the test dataset (100% object detection). The model predicted the malignancy risk with a sensitivity of 73.9%, specificity of 70.8%, positive predictive value (PPV) of 70.8%, negative predictive value (NPV) of 73.9% and accuracy of 66.772.4% during the testing. The radiologists performed with a sensitivity of 52.1±4.4%, specificity of 65.2±6.4%, PPV of 59.1±3.5%, NPV of 58.7±1.8%, and accuracy of 58.8±2.5% when using TI-RADS and sensitivity of 53.6±17.6% (p=0.87), specificity of 83.3±7.2% (p=0.06), PPV of 75.7±8.5% (p=0.13), NPV of 66.0±8.8% (p=0.31), and accuracy of 68.7±7.4% (p=0.21) when using AI-modified TI-RADS. Conclusions: Incorporation of AI into TI-RADS improved radiologist performance and showed better malignancy risk prediction than AI alone when classifying thyroid nodules. Employing AI in existing thyroid nodule classification systems may help more accurately identifying high-risk nodules.